(untitled) (Research, Society and Development, 2021)
Introduction: Humanized childbirth has several aspects that can be explored in its most varied dimensions, in ways that integrate with each other, aiming to promote healthy delivery and birth, as well as the prevention of morbidity and mortality through a set of adopted procedures and conducts. Objective: To demonstrate the assistance of nurses in conducting humanized childbirth. Methodology: The study was conducted based on qualitative research, descriptive through an Integrative Literature Review (RIL). The study was carried out through a search in the Virtual Health Library (VHL), accessing the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), and Nursing Database (BDENF), was performed in scientific articles published and available in journals from 2015 to 2020. Discussion of results: Based on the inclusion and exclusion criteria established in the methodology, 12 articles were selected for the integrative literature review. Data analysis was performed using Bardin’s Content Analysis. Final considerations: In order for there to be quality clinical care in the birth process, it is necessary to implement measures aimed at reducing the practice of invasive methods, which can be achieved through the continued training of professionals working in this area, in addition to adequacy of the institution’s structural factor to the parturient. In this way, the result is the provision of care in a humanized way, welcoming and satisfying the service offered.